2001
DOI: 10.1063/1.1370535
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic properties of GaMnAs layers with high Mn-content grown by migration-enhanced epitaxy on GaAs(100) substrates

Abstract: Ferromagnetic GaMnAs containing up to 10% Mn has been grown by migration-enhanced epitaxy at a substrate temperature of 150 °C. The lattice constant of hypothetical zinc-blende structure MnAs is determined to be 5.90 Å, which deviates somewhat from previously reported values. This deviation is ascribed to growth-condition-dependent density of point defects. Magnetization measurements showed an onset of ferromagnetic ordering around 75 K for the GaMnAs layer with 10% Mn. This means that the trend of falling Cur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
36
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 21 publications
3
36
0
Order By: Relevance
“…The Mn ion in the substitutional position in the GaAs lattice (Mn Ga ) acts as an acceptor, but in all Ga 1-x Mn x As samples the hole concentration is substantially lower than the Mn content. This has been ascribed to the presence of compensating donors, in particular to the formation of arsenic antisites (As Ga ) during the epitaxial growth of Ga 1-x Mn x As at As overpressure 16,17 . In Ref.7,9 and 18 the observed annealing-induced changes of the T C were attributed solely to the decrease of the concentration of arsenic antisites leading to the increase of the hole concentration.…”
mentioning
confidence: 99%
“…The Mn ion in the substitutional position in the GaAs lattice (Mn Ga ) acts as an acceptor, but in all Ga 1-x Mn x As samples the hole concentration is substantially lower than the Mn content. This has been ascribed to the presence of compensating donors, in particular to the formation of arsenic antisites (As Ga ) during the epitaxial growth of Ga 1-x Mn x As at As overpressure 16,17 . In Ref.7,9 and 18 the observed annealing-induced changes of the T C were attributed solely to the decrease of the concentration of arsenic antisites leading to the increase of the hole concentration.…”
mentioning
confidence: 99%
“…Gallium arsenide (GaAs) has several properties, so it is superior to silicon for use in optoelectronic devices. Increasing attention has been paid to the preparation of diluted magnetic semiconductors (DMS), in recent years after the III-V-based DMS, such as (In, Mn)As and (Ga, Mn)As, has been successfully fabricated by low-temperature MBE [2][3][4][5]. The ferromagnetic transition temperature (T c ) has increased a little by optimal annealing study [6] in comparison with the highest reported T c ¼ 110 K.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 However, there is lack of a direct measure of the depth dependent strain or distortion in GaMnAs epilayers. Ion beam analysis combined with the channeling technique can provide a possible solution.…”
Section: Introductionmentioning
confidence: 99%